Blocking IRES-mediated translation pathway as a new method to treat Alzheimer's disease. Issue 1 (March 2015) - Liu, Q.Y.
Graphical abstract: Highlights: Amyloid precursor protein can be synthesized via IRES-mediated translation/eIF2α-independent manner under cell stress. The blockage of this translation might be a new high-level specificity treatment for Alzheimer's disease. Abstract: Scientists theorized that β-amyloid (Aβ) plaques and tau tangles are involved in the development of Alzheimer's disease (AD), and amyloid precursor protein (APP) produces Aβ to trigger the disease process. However, the normal synaptic function of APP itself is not fully understood. Several findings cast APP as a potential key player in learning and memory under normal condition. Nevertheless, the regular operation of APP will be disrupted by abnormal accumulation of Aβ under cellular pathological conditions. Herein, there is a hypothesis that AD could be treated by attenuating APP synthesis during cellular pathophysiological stress. In virtue of a previous study, it was speculated that cells could not decrease APP synthesis via self-protection maybe because APP is synthesized via internal ribosome entry segment (IRES)-mediated translation. Consequently, the blockage of this translation might be a new inoffensive and high-level specificity treatment.